Development of a clothes folding machine / Azlan Shah Kamarul Kalai and Nor Liawati Abu Othman - Kamarul Kalai, Azlan Shah; Abu Othman, Nor Liawati (School of Mechanical Engineering, 2023)
This project is to help people to save money, save time, and for people who live in rural areas. Due to this, people who live in rural areas don’t usually have stable electricity and cut their cost for laundry because it relates with electric and water bills. The objectives for this project are to design and analyze an efficient pedal powered washing machine and to fabricate the pedal powered washing machine similar to the design made. The methodology used is the Morphological Analysis to generate the final design, internet for research and journals as guidance. The final product shows how the machine functions as well as its detailed fabrication.